A Systematic Risk Assessment and Meta-Analysis on the Use of Oral β-Alanine Supplementation - Dolan, Eimear (Adv Nutr, 2019)
β-Alanine supplementation is one of the world's most commonly used sports supplements, and its use as a nutritional strategy in other populations is ever-increasing, due to evidence of pleiotropic ergogenic and therapeutic benefits. Despite its widespread use, there is only limited understanding of potential adverse effects. To address this, a systematic risk assessment and meta-analysis was undertaken. Four databases were searched using keywords and Medical Subject Headings. All human and animal studies that investigated an isolated, oral, β-alanine supplementation strategy were included. Data were extracted according to 5 main outcomes, including 1) side effects reported during longitudinal trials, 2) side effects reported during acute trials, 3) effect of supplementation on circulating health-related biomarkers, 4) effect of supplementation on skeletal muscle taurine and histidine concentration, and 5) outcomes from animal trials. Quality of evidence for outcomes was ascertained using the Grading of Recommendations Assessment Development and Evaluation (GRADE) framework, and all quantitative data were meta-analyzed using multilevel models grounded in Bayesian principles. In total, 101 human and 50 animal studies were included. Paraesthesia was the only reported side effect and had an estimated OR of 8.9 [95% credible interval (CrI): 2.2, 32.6] with supplementation relative to placebo. Participants in active treatment groups experienced similar dropout rates to those receiving the placebo treatment. β-Alanine supplementation caused a small increase in circulating alanine aminotransferase concentration (effect size, ES: 0.274, CrI: 0.04, 0.527), although mean data remained well within clinical reference ranges. Meta-analysis of human data showed no main effect of β-alanine supplementation on skeletal muscle taurine (ES: 0.156; 95% CrI: −0.38, 0.72) or histidine (ES: −0.15; 95% CrI: −0.64, 0.33) concentration. A main effect of β-alanine supplementation on taurine concentration was reported for murine models, but only when the daily dose was ≥3% β-alanine in drinking water. The results of this review indicate that β-alanine supplementation within the doses used in the available research designs, does not adversely affect those consuming it.